FOR/WITH New York City, 15–16 November 2019 THE STORY OF ONE OF MY FOLLIES New York City, 16 November 2019. (April 2020) - Power, Ian
Abstract : In two nights in New York, I saw three world premieres and four other recent pieces at two very different concerts. Friday, 15 November at Issue Project Room in Brooklyn was the concert FOR, the first of two nights called FOR/WITH curated by the trumpeter Nate Wooley. The venue was celebrating the life of its late founder, the artist Suzanne Fiol, and her work was displayed around the hall with an appropriate sense of reverence and intensity. Wooley featured a composer I admire, Eva-Maria Houben of the Wandelweiser collective, and an uncharacteristic solo trumpet piece that she wrote for him called chanting ballads . Like most of Houben's work it was stark, simple and repetitive, and seemed to place the performer in a battle with himself, its briefly sustained tones becoming daunting events, spaced as far apart from each other as they were. Unlike most of Houben's work, it took advantage of the trumpet's entire range of pitch and dynamic, which at first seems to be entirely out of place with the atmosphere of the work, but, as it goes on, one of course realizes that this is the point and there is so much in these bare, somewhat awkward trumpet sounds to listen for. Every extraneous sound – both from the trumpet and from the hall – becomes part of the piece. My mind moves to curation: does Houben's music demand more control over a concert? No phones maybe? I feel for the performer: while the work does what I love most about solo works, which is to take us out of the regular 'concert' feeling and give us the sense that we're witnessing a ritual with a strange tool, I then end up focusing on the performer's unintentional ornamentation. A few clammed notes: are they supposed to illustrate the fragility of the instrument, its tone and its user, or are they also intended as part of any tool's thorough exploration? I've played Houben: it's hard. I get it. But I do think the point is to be charitable as a listener and enjoy every sound equally, in an attempt to divorce oneself from preconceived notions of 'successful' playing. What at first seemed like quite an awkward undertaking became an empowering experience for me, and, one hopes, for Wooley as well.